Answer:
1`. y = 4x+6
2. y = -6x + 29
3. y= 3x+1
4. y = x -2
5. y = 11.5x+ 3
6. y = -2x -4
Step-by-step explanation:
Answer:
y=x+2
Step-by-step explanation:
y-y1=m(x-x1)
y-2=1(x-0)
y-2=1(x)
y-2=x
y=x+2
Answer:
x=75
Step-by-step explanation:
Hey There!
If you didn't know the exterior angle of a triangle is equal to the sum of the opposite interior angles of a triangle
So essentially what I'm saying is that
2x-5=70+x
step 1 add 5 to each side
-5+5 cancels out
70+5=75
now we have
2x=70+x
step 2 subtract x from each side
x-x cancels out
2x-x=x
we're left with
x=75
Because the graph is shifted up three units from the original mother function (f(x) = log x), and therefore, the answer is f(x) = log x + 3.